Tumor necrosis factor alpha (TNFα)-binding imprinted polymers. A non-systemic therapeutic approach for inflammatory bowel diseases - Rina Arad Yellin; Anett Hudák; Tamás Letoha; Bernard S. Green (Elsevier, 2023)
We report a multi-step approach for the synthesis of protein-imprinted polymeric particles that selectively bind tumor necrosis factor alpha (TNFα). With high affinity for TNF-α, this type of polymer may provide a novel, safe treatment or preventive approach for addressing inflammatory bowel diseases (e.g., Crohn's disease, ulcerative colitis).A key element in the approach is the use of functional monomers (FMs) based on the amino acid tyrosine, known to play a uniquely dominant role in antibody combining sites and providing high affinity for the protein. TNFα binding in the, not yet optimized, PIP particles were found to be 14 times that of the NIPs.In vitro experiments with TNFα imprinted polymers indicated no toxicity towards L929 and Caco-2 reporter cell lines and effective in reducing TNFα-induced cell death. The results corroborate the potential of such particles to treat, or prevent, inflammatory bowel diseases, currently treated with systemically delivered biologics. The results bode well for the general development of non-systemic, orally delivered and safe, imprinted polymeric drugs that can act in the gastrointestinal tract where antibodies cannot readily be used.